2020
DOI: 10.3847/1538-4357/ab8223
|View full text |Cite
|
Sign up to set email alerts
|

Scattering-induced Intensity Reduction: Large Mass Content with Small Grains in the Inner Region of the TW Hya disk

Abstract: Dust continuum observation is one of the best methods to constrain the properties of protoplanetary disks. Recent theoretical studies have suggested that the dust scattering at the millimeter wavelength potentially reduces the observed intensity, which results in an underestimate in the dust mass. We investigate whether the dust scattering indeed reduces the observed continuum intensity by comparing the ALMA archival data of the TW Hya disk at Band 3, 4, 6, 7 and 9 to models obtained by radiative transfer simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 65 publications
7
48
2
Order By: Relevance
“…This indicates that our model has a too high scattering opacity at millimetre wavelengths and therefore overestimates the total dust optical depth τ ext d within the rings. However, our dust model fits the data because scattering can reduce the observed dust emission as has been shown by Zhu et al (2019), Liu (2019) and Ueda et al (2020). Consequently, the model overestimates the absorption of the back side 12 CO J = 2−1 line emission, resulting in too weak line emission at the location of the dust rings (see Fig.…”
Section: Contribution Of the Back Side Of The Diskmentioning
confidence: 70%
“…This indicates that our model has a too high scattering opacity at millimetre wavelengths and therefore overestimates the total dust optical depth τ ext d within the rings. However, our dust model fits the data because scattering can reduce the observed dust emission as has been shown by Zhu et al (2019), Liu (2019) and Ueda et al (2020). Consequently, the model overestimates the absorption of the back side 12 CO J = 2−1 line emission, resulting in too weak line emission at the location of the dust rings (see Fig.…”
Section: Contribution Of the Back Side Of The Diskmentioning
confidence: 70%
“…All of these factors contribute independently and can decrease or increase the reported values within a factor of a few (Ballering & Eisner 2019). Further, given that at the scales of the observed circumstellar disks, dust scattering can decrease the intensity at millimeter wavelengths, which are likely also optically thick, our estimates for the mass of the compact sources should be taken as conservative lower limits (Liu 2019;Ueda et al 2020). The order of magnitude of the lower limits reported here is comparable to other compact (40 au) circumstellar disks in Class I multiple systems observed at high (25 au) resolution, derived in a similar fashion (Takakuwa et al 2017;Alves et al 2019;Cruz-Sáenz de Miera et al 2019).…”
Section: Masses From 3 MM Continuum Emissionmentioning
confidence: 94%
“…Interestingly, recent multiwavelength studies of the Atacama Large Millimeter/submillimeter Array (ALMA) have shown that Ar in Solids ring and gap structures reside even in the optically thick region (Carrasco-González et al 2019;Macías et al 2021). This implies that the substructures are induced by the temperature variation and/or intensity reduction from scattering (e.g., Liu 2019;Zhu et al 2019;Sierra & Lizano 2020;Ueda et al 2020), not by the density variation. For example, the HL Tau disk has a gap at ∼13 AU at the wavelength where the region is expected to be optically thick (Carrasco-González et al 2019).…”
Section: Implications From Disk Observationsmentioning
confidence: 99%